2019
DOI: 10.29328/journal.jcn.1001032
|View full text |Cite
|
Sign up to set email alerts
|

Urinary NGAL incorporation into Renal Angina Index for early detection of acute kidney injury in critically ill children

Abstract: Background and objectives: New AKI biomarkers (on the top of it NGAL biomarker) have demonstrated better performance for prediction of AKI in critically ill patients with heterogeneous illness. Renal angina index was recently reported to enhance prediction of severe AKI at the time of intensive care unit admission. This study tested the hypothesis that incorporation of uNGAL in patients with renal angina improves the prediction of severe AKI. Design, setting, participants & measurements:In our study 53critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
4
1
1
Order By: Relevance
“…Unlike us, other authors [ 4 , 9 , 16 ] have demonstrated that the association of increased uNGAL + RAI ≥ 8 significantly increases the prediction for subsequent AKI. Individual uNGAL demonstrated marginal discrimination for severe AKI (AUC = 0.877, little higher than the prediction by RAI (AUC = 0.847), but the incorporation of uNGAL to the RAI significantly increased the AKI prediction (AUC = 0.847, increased to 0.893) [ 4 ]. Other authors also did not find an increased AKI prediction of such combination [ 19 ].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Unlike us, other authors [ 4 , 9 , 16 ] have demonstrated that the association of increased uNGAL + RAI ≥ 8 significantly increases the prediction for subsequent AKI. Individual uNGAL demonstrated marginal discrimination for severe AKI (AUC = 0.877, little higher than the prediction by RAI (AUC = 0.847), but the incorporation of uNGAL to the RAI significantly increased the AKI prediction (AUC = 0.847, increased to 0.893) [ 4 ]. Other authors also did not find an increased AKI prediction of such combination [ 19 ].…”
Section: Discussioncontrasting
confidence: 54%
“…The RAI score was calculated on day 1 of PICU admission. We recorded the RAI index in both ways: as a continuous variable from 1 to 40 as well as a categorical variable (dichotomous); a RAI score of ≥8 was considered as a positive index [ 4 ] We were looking for associations of uNGAL values from day 1 with CrCl from day 1 and from day 3 as well as the RAI score with the day 1 CrCl, and multiple regression RAI + NGAL as the independent and CrCl as the dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…We present an experimental approach that utilizes biomarkers to enable early and sensitive detection of AKI resulting from HIE. Urinary NGAL has been established as an early responding biomarker of AKI, not only in rats following early ischemic AKI and in mice from cisplatin toxicity (Mishra et al, 2003(Mishra et al, , 2004, but also in both adult and pediatric patients after cardiac surgery (Mishra et al, 2005;Wagener et al, 2006), and in critically ill children with heterogeneous illness (Zeid et al, 2019). In both preclinical experiments and in clinical studies of pediatric cohorts, NGAL elevation preceded rises in other early responding markers (Mishra et al, 2003), and this is in line with our observations showing significant increases in NGAL as early as 1 day following injury, the earliest time point assayed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the incorporation of other indicators of kidney injury can further increase the predictive power of RAI. Fluid overload [ 18 ], urinary neutrophil gelatinase-associated lipocalin [ 19 ] and urinary L-type fatty acid-binding protein [ 20 ] combined with RAI have been shown to optimize AKI prediction in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%